The Effect of Learning Model Advance Organizer Toward Students’ Science Learning Achievement Class VII SMPN 22 Padang - AMERIA YUNITA; Dezi Handayani; Syamsurizal Syamsurizal (Bioeducation Journal, 2018)
This research is based on the problems that exist in SMPN 22 Padang is the selection of less precise learning model, students' science learning outcomes are still low. Efforts that can be done is to apply advanced organizer learning model on global warming material in SMPN 22 Padang. The purpose of this study is to determine the effect of the implementation of advanced organizer learning model on the results of science learning class VII SMPN 22 Padang. This type of research is experimental research with Randomized Control Group Posttest Only Design research design. Population in this research is all class VII at SMPN 22 Padang registered in Academic Year 2017/2018 amounted to eight class. Sampling was done by using purposive sampling technique, which selected as research sample is class VII.8 as experiment class and class VII.7 as control class. The instrument used is a matter of posttest for knowledge competence. The hypothesis in this study was tested using t-test. Based on the results of research and discussion can be concluded: the implementation of learning model Advance Organizer can improve student learning outcomes (knowledge competence) in SMPN 22 Padang.